2022
DOI: 10.1002/arco.5266
|View full text |Cite
|
Sign up to set email alerts
|

MicroCT scanning and direct AMS dating of charred sweet potato (Ipomoea batatas) fragments from Nombe rockshelter in the highlands of Papua New Guinea

Abstract: Here, we report on the results of microCT scanning and Accelerator Mass Spectrometry (AMS) radiocarbon dating of fragments of charred archaeological parenchyma collected from surface deposits at Nombe rockshelter in the highlands of Papua New Guinea. Five fragments are taxonomically identified as sweet potato (Ipomoea batatas). Two subsamples from the largest fragment yield a combined AMS date range of c. 300-148 calBP (with median probabilities of 187 and 195 calBP respectively). Although post-dating European… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The recording process found that several characteristics previously used to identify archaeological parenchyma tissues, such as cell size and shape, were of little diagnostic value for differentiating species or families (diagnostic characteristics used here are provided in Table 3). It was found that the ranges were too great within individual samples, as well as between samples from the same species, resulting in significant overlap (Pritchard, 2018; Barron et al., 2022). Therefore, these characteristics are not considered diagnostic features here.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The recording process found that several characteristics previously used to identify archaeological parenchyma tissues, such as cell size and shape, were of little diagnostic value for differentiating species or families (diagnostic characteristics used here are provided in Table 3). It was found that the ranges were too great within individual samples, as well as between samples from the same species, resulting in significant overlap (Pritchard, 2018; Barron et al., 2022). Therefore, these characteristics are not considered diagnostic features here.…”
Section: Resultsmentioning
confidence: 99%
“…The most distinctive fire damage occurs in sweet potato, where large radial tears appear in the pith adjacent to the outer surface (Hather & Kirch, 1991; Pritchard et al., 2018). If these tears appear in the pith radially adjacent to attached cortex cells, which are also radially aligned with the cells in the pith, then these features together can be indicative of sweet potato (see Barron et al., 2022). However, charring patterns can vary considerably depending upon the initial state of the USO (wet, moist, dried), intensity and extent of burning or charring, and presumably based on preservation in different burial conditions, as well as intra‐taxa morphological disposition; thus, charring patterns should not ordinarily be relied upon as the sole diagnostic characteristic for a fragment of archaeological parenchyma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, these case studies are designed to exemplify the value of archaeobotany to mainstream archaeological endeavours. Barron et al (2022) apply the microCT-based method for the investigation of archaeological parenchyma to macrobotanical fragments recovered from recent deposits at Nombe rockshelter in the highlands of Papua New Guinea. Five fragments were taxonomically identified to be sweet potato (Ipomoea batatas), one of which was directly AMS dated to c.300-150 calBP.…”
Section: Overviewmentioning
confidence: 99%